Factors associated with social responsibility among university students in Yala, Thailand during the COVID-19 pandemic - Awirut Singkun (College of Public Health Sciences, Chulalongkorn University, 2021)
Purpose - The objectives of this study were to evaluate knowledge on the coronavirus disease 2019 (COVID-19) transmission, attitude toward the measures of COVID-19 prevention and control, explore social responsibility behaviors and test for the association between variables and social responsibility among university students. Design/methodology/approach - It was a cross-sectional study. The population was 7,754 students from a university in Yala province. The sample size was 370 students according to Krejcie and Morgan table. Google form was introduced to make the self-administered questionnaires. Content validity was evaluated by three experts, and for reliability of knowledge and attitude, the coefficient was 0.707 and 0.702. Data collection was done in the early April 2020. Descriptive statistics and χ² were used to analyze the data. Ethical approval number 095-63. Findings - The results found that students' knowledge on COVID-19 transmission was in a moderate level, attitude toward the state measures for COVID-19 prevention and control was at a high level. Their social responsibility behaviors were at a high level. Their knowledge, attitude and payment were significant association with social responsibility behaviors among university students (p < 0.05). Originality/value - University students' knowledge on disease transmission as well as positive attitude toward the measures of regulation led them to have cooperation. Social distancing and lockdown measures affected their lifestyle. However, they have responsibility behaviors to the society, especially in the pandemic situation.